Roughness Coefficient of Micro-irrigation Laterals - Mohd Soom, Mohd Amin (Universiti Putra Malaysia Press, 1994)
A micro-irrigation system' must apply water and fertilizer uniformly over the entire field. However friction loss in pipes and fittings, and differences in elevation cause water pressure to vary. Discharge variations due to pressure differences and manufacturing variations cause non-uniformity of irrigation. To assure maximum economy, the hydraulic design of the system must be adequately evaluated for the required level of uniformity. This paper presents results of laboratory tests for head loss in smooth polyethylene pipe fitted with insert emitters. The Hazen-Williams roughness coefficients are included in the friction factor-Reynolds number diagrams so that system designers may choose a more accurate friction coefficient to improve energy, water and material use efficiency of a micro-irrigation system.